Analisis Kebijakan Ekonomi dan Kesejahteraan Sosial Perspektif Maqashid Asy-syariah (Studi Pasal 88 UU Nomor 11 Tahun 2020) - Ma'ruf Hidayat (Jurnal Penelitian Agama, 2021)
The coverage of the draft Law on Job Creation has drawn polemics from a number of parties, one of which is from workers who have taken action against regulations related to labor clusters which have changed many articles in Law Number 13 of 2003 concerning Manpower. This paper examines the implications of the Work Creation Omnibus Law Bill from the perspective of maqasid sharia which focuses on labor issues. This type of research is included in qualitative research in the form of descriptive, which explains some of the articles of the Omnibus law Cipta Kerja. The method used to obtain data is a normative juridical approach in the form of primary legal material, namely Law no. 11 of 2020 concerning Job Creation. Then for the collection and data analysis methods using descriptive analytical. The results of the study show that the concept of welfare in the omnibus law refers to the labor law where every worker has the right to earn income that meets a decent living, this is self-intersest and material oriented, while in the concept of Maqashid syariah is an orientation to maslahah which covers all aspects. human life which includes protection of religion, soul, descent, wealth, reason.